Correlation between upper and lower airway inflammations in patients with combined allergic rhinitis and asthma syndrome: A comparison of patients initially presenting with allergic rhinitis and those initially presenting with asthma - Xia, Shu (Exp Ther Med, 2018)
Allergic rhinitis (AR) and asthma often coexist. The terminology combined allergic rhinitis and asthma syndrome (CARAS) was introduced to describe patients with combined AR and asthma. The aim of the present study was to evaluate the correlation between eosinophilic inflammation in the upper and lower airways of patients with CARAS. Stable patients with CARAS initially presenting with AR or asthma were recruited. Healthy subjects and patients with AR alone were recruited as controls. Clinical characteristics, including disease history, lung function, nasal airway inspiratory resistance and upper and lower airway eosinophilic inflammation were evaluated and compared. A total of 73 subjects (22 patients with CARAS initially presenting with AR, 15 patients with CARAS initially presenting with asthma, 25 patients with AR alone and 11 healthy subjects) were studied. The nasal symptoms visual analogue scale scores at the week prior to enrollment and nasal airway inspiratory resistances were comparable among the groups. The percentage of predicted forced expiratory volume in 1 sec and percentage of predicted maximal middle expiratory flow in patients with CARAS initially presenting with asthma were significantly lower compared with the other three groups (P<0.05). No significant different in the percentage of eosinophils in the nasal lavage was observed between patients with CARAS and those with AR only; however, it was significantly increased compared with healthy subjects (P<0.05). The fractional concentration of exhaled nitric oxide and percentage of eosinophils in the sputum were significantly increased in patients with CARAS compared with those in the AR only and healthy subject groups (P<0.05). The difference in the percentage of eosinophils in the nasal lavage and sputum between patients with CARAS initially presenting with AR and initially presenting with asthma was not significant; however, a positive correlation between the percentage of eosinophils in the upper and lower airways was present in patients with CARAS initially presenting with AR only (r=0.526, P=0.030).